Risk factors for an early dialysis start in patients with diabetic nephropathy end-stage renal disease - Mizuno T; Hayashi T; Kato R; Noguchi A; Hayashi H; Yuzawa Y; Yamada S; Nagamatsu T (Dove Medical Press, 2014)
Tomohiro Mizuno,1,2,* Takahiro Hayashi,3,* Rina Kato,1 Ayaka Noguchi,1 Hiroki Hayashi,2 Yukio Yuzawa,2 Shigeki Yamada,3 Tadashi Nagamatsu1 1Department of Analytical Pharmacology, Meijo University Faculty of Pharmacy, Nagoya; 2Department of Nephrology, 3Department of Clinical Pharmacy, School of Medicine, Fujita Health University, Toyoake, Japan *These authors contributed equally to this work Background: Patients with end-stage renal disease (ESRD) have symptoms related to severe anemia, edema, and heart failure. Although dialysis improves ESRD syndromes, the optimum timing for initiation of dialysis is unclear. Recent observational studies have suggested that early commencement of dialysis can be harmful. Given that early dialysis may increase the risk of death, avoiding an early start to dialysis is recommended. Patients with diabetic nephropathy (DN) may have risk factors for early dialysis. However, the risk factors for early dialysis are unclear in ESRD patients with DN. The aim of this study was to elucidate the risk factors for early initiation of dialysis in patients with DN and ESRD. Methods: From April 2009 to December 2012, we identified Japanese DN patients with an estimated glomerular filtration rate of less than 15 mL/minute/1.73 m2. The patients were divided into late or early dialysis groups based on the timing of start of dialysis. Results: We evaluated 52 patients who commenced dialysis during the observation period, including 33 in the late dialysis group and 19 in the early dialysis group. There was a significant association between early dialysis and age ≥65 years (odds ratio 4.59). The incidence of pneumonia before starting dialysis was significantly higher in elderly patients than in nonelderly patients. Conclusion: Our findings suggest that elderly patients with DN and ESRD have an increased risk of early initiation of dialysis, and occurrence of pneumonia is also associated with early dialysis. To avoid early commencement of dialysis, booster pneumococcal vaccination could be useful in elderly DN patients with ESRD. Keywords: early dialysis, diabetes mellitus, nephropathy, elderly patients, estimated glomerular filtration rate